2022
DOI: 10.1149/1945-7111/ac4b1d
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Simvastatin by Voltammetry Method at Screen-Printed Electrode Modified by Graphene Oxide Nanosheets and Sodium Dodecyl Sulfate

Abstract: An accurate, rapid, simple, and novel technique was developed to determine simvastatin (SMV). In this research, a screen-printed electrode (SPE) was deposited with graphene oxide (GO) and sodium dodecyl sulfate (SDS), respectively. For the first time, the handmade modified SPE measured the SMV by differential pulse voltammetry (DPV) with high sensitivity and selectivity. The results of cyclic voltammetry indicated the oxidation irreversible process of SMV. Various parameters (pH, concentration, scan rate, supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…In the case of rosuvastatin, it was observed that the current intensity decreases with increasing pH, while for simvastatin, the highest and well-defined current was obtained at pH = 7.0 (Figures 3 and S4). These results are consistent with previously published studies [44,45]. As can be seen, an oxidation process was triggered at 0.58 V for SPCE and 0.65 V for AuNP-MWCNTs/SPCE during anodic scanning.…”
Section: Study Of the Electrochemical Behavior Of The Sensors In Rosu...supporting
confidence: 93%
See 1 more Smart Citation
“…In the case of rosuvastatin, it was observed that the current intensity decreases with increasing pH, while for simvastatin, the highest and well-defined current was obtained at pH = 7.0 (Figures 3 and S4). These results are consistent with previously published studies [44,45]. As can be seen, an oxidation process was triggered at 0.58 V for SPCE and 0.65 V for AuNP-MWCNTs/SPCE during anodic scanning.…”
Section: Study Of the Electrochemical Behavior Of The Sensors In Rosu...supporting
confidence: 93%
“…Moreover, the results demonstrate the feasibility of the voltammetric method for the analysis of the two statins. The obtained values are similar or even better than those reported in the literature [6,[27][28][29]44,49,50] (Table 4), which proves that the AuNP-MWCNTs/SPCE sensor has adequate electroanalytical performance for RV and SV quantification in actual samples. The association of carbon nanotubes and gold nanoparticles demonstrated in all stages of the study that it is an efficient way to improve the electrochemical performance of the modified sensor.…”
Section: Determination Of Lod and Loqsupporting
confidence: 85%
“…Current knowledge reveals several techniques for detecting heavy metal ions in water, but fluorescent probes and electrochemical sensors still represent the best choice owing to their numerous advantages such as low cost, rapid response time, biocompatibility, and ease of modification. 5,6 Chemical processes including oxidation and photodegradation have associated issues such as high costs and energy consumption, with the risk of undesired by-products. 7 Biological methods, i.e.…”
Section: Introductionmentioning
confidence: 99%